Exploring the Emergency Planning Requirements: A Qualitative Research Study at the Kingdom of Saudi Arabia - Alrehaili, Naif R (International Journal of Disaster Management, 2023)
This study aimed to explore emergency planning requirements for managing disasters in the Kingdom of Saudi Arabia (KSA). The study adopted interpretivism; an inductive approach; a descriptive survey; and qualitative methods to address its aim. The techniques used included a literature review and semi-structured interviews. The study sample consisted of 13 experts from the KSA General Directorate of Civil Defense (GDCD). The data were analyzed by using content analysis. The study findings revealed that the emergency planning requirements are administrative requirements, including regulations and legislation; technical requirements, which include equipment; human resources, including staff and responders; identifying, analyzing, and evaluating risks; determining the tasks and responsibilities of the relevant agencies and stakeholders; qualified leadership; determining the chain of command at national and local levels; coordination and cooperation among stakeholders; knowledge gained from local or international experiences; updated database; the availability of sufficient financial resources; completed infrastructure; and improved training and practice. The study also found that although emergency planning requirements are more or less in place, there is a need for further improvement and development; specifically, there is a need for better understanding, knowledge, and awareness. Consequently, it strongly recommends that all emergency planning requirements developed from this study should be implemented simultaneously and as an integrated whole. By doing so, it could help decision-makers and emergency planners at government emergency agencies to improve, develop, and reinforce emergency planning, specifically in reducing disaster risks.